Review on Machine Learning Based Suggestion System - Sharma, Ankit; Ekta (International Journal of Computer Sciences and Engineering, 2025)
Suggestion system plays vital role in WWW world and used in many applications. It has created the collection of many application, created global village and growth for numerous information. This paper represents the overview of Approaches and techniques generated in Suggestion system. Suggestion system is divided into three main types Collaborative Filtering, Content based and hybrid-based Method. The work in our categories collaborative filtering as Memory based type and Model based type. The paper discusses in detail the methods, their pros and cons. The paper proves to be a milestone in the research field of suggestion system.